Does dynamic federalism yield compatible policies? A study of the designs of federal and state vehicle policies. Issue 3 (3rd July 2018) - Siddiki, Saba; Carley, Sanya; Zirogiannis, Nikolaos; Duncan, Denvil; Graham, John
Abstract: Governance systems that allow jurisdictions housed at different levels to develop policies pertaining to common issues can foster the development of innovative and contextually appropriate solutions. Sometimes, however, the policies that emerge from different levels of government with overlapping policy jurisdiction can offer mixed, even contradictory, messages to policy targets. In such cases, the potential to achieve goals that are common among different policies may be compromised. This potentiality prompts questions about the extent to which policies developed at different levels of government relating to the same issue are mutually reinforcing, or compatible. In this paper, we investigate compatibility among a set of federal and state vehicle environmental performance standards in terms of policy goals, instruments, and incentives. The study entails a descriptive, qualitative analysis of federal fuel economy and vehicle greenhouse gas standards, and policies contained in California's Advanced Clear Car Program.